Application of Circulation Controlled Blades for Vertical Axis Wind Turbines - Shires, Andrew; Kourkoulis, Velissarios (MDPI, 2013)
The blades of a vertical axis wind turbine (VAWT) rotor see an inconsistent angle of attack through its rotation. Consequently, VAWT blades generally use symmetrical aerofoils with a lower lift-to-drag ratio than cambered aerofoils tailored to maximise horizontal axis wind turbine rotor performance. This paper considers the feasibility of circulation controlled (CC) VAWT blades, using a tangential air jet to provide lift and therefore power augmentation. However CC blade sections require a higher trailing-edge thickness than conventional sections giving rise to additional base drag. The choice of design parameters is a compromise between lift augmentation, additional base drag as well as the power required to pump the air jet. Although CC technology has been investigated for many years, particularly for aerospace applications, few researchers have considered VAWT applications. This paper considers the feasibility of the technology, using Computational Fluid Dynamics to evaluate a baseline CC aerofoil with different trailing-edge ellipse shapes. Lift and drag increments due to CC are considered within a momentum based turbine model to determine net power production. The study found that for modest momentum coefficients significant net power augmentation can be achieved with a relatively simple aerofoil geometry if blowing is controlled through the blades rotation.
Keywords: VAWT; wind turbine; aerodynamics; circulation control; flow control; lift augmentation